Innoverende toegangsroetes in selfoonwoordeboeke - du Plessis, André H. (Lexikos, 2022)
Innovative Access Structures in Mobile Dictionaries. The access structure of any dictionary is an important one. It provides the user with a means to obtain the required data or to extract valuable information. This dictionary structure mostly overlaps with other structures such as the macro-, micro- and mediostructure, which in turn creates different access routes a dictionary user can follow to try and satisfy his or her lexicographic needs. In printed dictionaries, the access structure can already be found on the cover, while in electronic or online dictionaries this structure is usually visible on the home or landing page (Du Plessis 2015: 51-52). Gouws and Prinsloo (2005: 64) differentiate between two types of access structures: the outer access structure, which relates to the access or search routes that lead a user to the lemma sign, and the inner access structure, which, among other things, involves the search routes and zones within a dictionary article. The traditional functions and uses of dictionary structures are adapted for the online and mobile medium in order to better satisfy user needs. The disadvantage of this, however, is that it is becoming increasingly difficult to distinguish between different dictionary structures (Müller-Spitzer 2013: 368-369). Fortunately, e-dictionaries have the freedom to provide new and innovative ways for users to access lexicographic material. The goal of this article is to highlight and evaluate some of these innovative access routes, particularly in mobile dictionaries. This is done to determine which access routes deserve further investigation or should be considered as a standard practice in mobile and other e-dictionaries. Keywords: access routes, access structure, cellphone dictionaries, dictionary structures, electronic dictionaries, e-lexicography, inner access structure, mobile applications, mobile dictionaries, mobile lexicography, outer access structure, search routes, smart phones